Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja Non Fisik dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Hanil Indonesia - Hargyatni, Titin; Kusumajaya, Robby Andika; Purwanti, Yuni Dwi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
Consumer behavior has changed from offline shopping to online. The e-commerce business is growing along with the rapid development of technology and information. Consumer purchasing decisions through online-based transactions, among others, need to consider Online consumer reviews (OCR) and trust. This study aims to determine the effect of OCR and trust on purchasing decisions at Tokopedia. The sample used was 100 respondents with random sampling technique. The data was processed using multiple linear regression analysis. The results showed that OCR and trust partially or simultaneously had a significant effect on purchasing decisions. OCR and trust are able to explain 86.4% of consumer perceptions in purchasing decisions, the remaining 13.6% is the influence of other factors that are not explained in this study.